La lección de matemáticas a través de estudios internacionales con videos - Ruiz, Angel (2011)
It is intended to support the use of Video Technology in Mathematics Education Research, and for that reason advantages and limitations of this tools are described. Three studies of videos are analyzed about the lessons in the Teaching of Mathematics. The first 2 studies were done within the Trends in International Mathematics and Science Study (TIMSS), and the third one, the Learners Perspective Study (LPS): by a team of researchers with a one more comprehensive methodology originally developed by David Clarke in Australia. By means of those studies we intend to detect some interesting elements for the practice of the Teaching of Mathematics. Global comparisons and reviews settle down on the significance of these studies. Additionally, a section about the characteristics of the Japanese Lesson is included, an issue which occupies an important place within these studies. The conclusions aim to emphasize strengths, problems and perspectives of this type of international comparative studies, in their close relation with the activity within the Mathematics classroom.